Pattern film, variable transmittance device including same, and method for manufacturing variable transmittance device
Patent Information
- Application Number
- JP2022514659
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-18
- Filing Date
- 2021-02-04
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-02-04
AI Technical Summary
【0015】 本出願の一実施態様に係るパターンフィルムは、スペーサパターンが隔壁スペーサおよびボールスペーサを含み、前記第1基材層の単位面積あたりの、前記スペーサパターンの単位面積比が5%以上17%以下であることで、セルギャップを維持すると同時に、特定の面積比を導入してこれを含む透過度可変デバイスの明暗差不良および配向不良を解決して、透過度可変フィルムの駆動が良好であることを特徴とする。
Smart Images

Figure 0007651813000002 
Figure 0007651813000003 
Figure 0007651813000004
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2020-0019488, filed with the Korean Intellectual Property Office on February 18, 2020, the entire contents of which are incorporated herein by reference.
[0002] The present specification relates to a patterned film, a variable transmission device including the same, and a method for manufacturing the variable transmission device. [Background technology]
[0003] The variable transmittance device may refer to a functional film that can adjust the transmittance of sunlight.
[0004] The variable transparency device means a device that can be switched between at least two or more different states. The applications of such devices are gradually expanding, for example, to eyewear such as glasses or sunglasses, mobile devices, wearable devices such as virtual reality (VR) devices and augmented reality (AR) devices, and sunroofs in vehicles.
[0005] The variable transmittance device can easily transmit or block light from the outside, and can be used as a light-shielding film for architectural smart windows, automobile sunroofs, and transparent displays. At this time, the variable transmittance device must maintain a certain cell gap between the two substrates.
[0006] Ball spacers are used to maintain the cell gap. However, when a film is placed vertically over a large area, gravity causes the liquid phase to shift to the bottom, resulting in poor appearance. As a result, in the field of variable transmittance devices, research is being conducted to solve the problem of poor appearance by using technology to pattern partition walls with a mesh or honeycomb structure.
[0007] Meanwhile, there are attempts to reduce the area of the spacers that do not participate in the change of transmittance in order to increase the visibility of the transmittance variable device. However, as the spacing between patterns becomes wider, a difference in the cell gap between the periphery of the patterns and the center between the patterns occurs, resulting in poor appearance. To solve this problem, research is also being conducted into introducing a conductive adhesive to the upper plate of the pattern of the transmittance variable device to fix the film flat and firmly.
[0008] As described above, in order to prepare a variable transmittance film, the pattern area needs to be optimized, and the pattern structure or manufacturing method also needs to be changed. This makes it necessary to solve the problem of driving the variable transmittance device due to poor contrast and poor orientation caused by not maintaining the cell gap.
[0009] Therefore, research is still ongoing to improve visibility of variable transmittance devices while maintaining the cell gap. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] European Patent Application Publication No. 0022311 Summary of the Invention [Problem to be solved by the invention]
[0011] The present specification relates to a patterned film, a variable transmission device including the same, and a method for manufacturing the variable transmission device. [Means for solving the problem]
[0012] One embodiment of the present application provides a pattern film comprising a first substrate layer and a plurality of spacer patterns formed on the first substrate layer, the spacer patterns including partition spacers and ball spacers, the ball spacers being embedded in or in contact with at least one of the partition spacers, and a unit area ratio of the spacer patterns per unit area of the first substrate layer being 5% or more and 17% or less.
[0013] In another embodiment, a variable transmittance device is provided, comprising a pattern film according to the present application and a second substrate arranged opposite the pattern film and maintained at a distance from the pattern film by the spacer pattern of the pattern film.
[0014] Finally, in one embodiment of the present application, there is provided a method for manufacturing a variable transmittance device, comprising the steps of: preparing a pattern film according to the present application; forming an alignment film on the first base layer on which the spacer pattern of the pattern film is formed so as to cover the spacer pattern to form a first laminate; forming an adhesive layer on top of a laminate including a second base layer and a transparent layer to form a second laminate; stacking the first laminate and the second laminate so that the adhesive layer of the second laminate contacts the spacer pattern side of the first laminate; and forming a light modulation layer between the first laminate and the second laminate. Effect of the Invention
[0015] The pattern film according to one embodiment of the present application is characterized in that the spacer pattern includes partition wall spacers and ball spacers, and the unit area ratio of the spacer pattern per unit area of the first substrate layer is 5% or more and 17% or less, thereby maintaining the cell gap while introducing a specific area ratio to solve poor light contrast and poor orientation of a variable transmittance device including the same, thereby providing good operation of the variable transmittance film. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a side view of a patterned film according to one embodiment of the present application. [Diagram 2] FIG. 2 is a diagram showing the configuration of a spacer pattern according to one embodiment of the present application. [Diagram 3] FIG. 2 is a diagram showing a stacked structure of a variable transmittance device according to an embodiment of the present application. [Figure 4] FIG. 13 illustrates a method for manipulating the 50% disorder of a square spacer pattern. [Diagram 5] FIG. 13 shows the pattern after manipulating the 50% disorder of the square spacer pattern. [Figure 6] 1A to 1C are diagrams illustrating a manufacturing process of a patterned film according to one embodiment of the present application. [Figure 7] FIG. 2 shows optical microscope images of the patterned film of Example 1 of the present application at 50 and 200 magnifications. [Figure 8] FIG. 2 shows optical microscope images at 50x and 200x magnification of the patterned film of Example 2 of the present application. [Figure 9] FIG. 2 shows optical microscope images at 50 and 200 magnifications of the patterned film of Comparative Example 1 of the present application. [Figure 10] FIG. 2 shows optical microscope images at 50 and 200 magnifications of the patterned film of Comparative Example 2 of the present application. [Figure 11] FIG. 2 is a diagram showing the appearance of a variable transmittance device to which the pattern film of Example 1 of the present application is applied, after being driven at 40 V. [Figure 12] FIG. 13 is a diagram showing the appearance of a variable transmittance device to which the pattern film of Example 2 of the present application is applied, after being driven at 40 V. [Figure 13] FIG. 2 is a diagram showing the appearance of a variable transmittance device to which the pattern film of Comparative Example 1 of the present application is applied, after being driven at 40 V. [Figure 14] FIG. 13 is a diagram showing the appearance of a variable transmittance device to which a pattern film according to Comparative Example 2 of the present application is applied, after being driven at 40 V. [Figure 15] FIG. 2 shows optical microscope images at 50x and 200x of the patterned film of Example 3 of the present application. [Figure 16] FIG. 1 shows optical microscope images at 50 and 200 magnifications of the patterned film of Example 4 of the present application. [Figure 17] FIG. 2 shows optical microscope images at 50 and 200 magnifications of the patterned film of Comparative Example 3 of the present application. [Figure 18] FIG. 2 shows optical microscope images at 50 and 200 magnifications of the patterned film of Comparative Example 4 of the present application. [Figure 19] FIG. 13 is a diagram showing the appearance of a variable transmittance device to which the pattern film of Example 3 of the present application is applied before driving (0 V). [Figure 20] FIG. 13 is a diagram showing the appearance of a variable transmittance device to which the pattern film of Example 4 of the present application is applied before driving (0 V). [Figure 21] FIG. 13 is a diagram showing the appearance of a variable transmittance device to which a pattern film of Comparative Example 3 of the present application is applied, before being driven (0 V). [Figure 22] FIG. 13 is a diagram showing the appearance of a variable transmittance device to which a pattern film according to Comparative Example 4 of the present application is applied, before driving (0 V). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present specification will be explained in more detail below.
[0018] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings in order to enable those skilled in the art to easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0019] One embodiment of the present application provides a pattern film comprising a first substrate layer and a plurality of spacer patterns formed on the first substrate layer, the spacer patterns including partition spacers and ball spacers, the ball spacers being embedded in or in contact with at least one of the partition spacers, and a unit area ratio of the spacer patterns per unit area of the first substrate layer being 5% or more and 17% or less.
[0020] The pattern film according to one embodiment of the present application is characterized in that the spacer pattern includes partition wall spacers and ball spacers, and the unit area ratio of the spacer pattern per unit area of the first substrate layer is 5% or more and 17% or less, thereby maintaining the cell gap while introducing a specific area ratio to solve poor light contrast and poor orientation of a variable transmittance device including the same, thereby providing good operation of the variable transmittance film.
[0021] In one embodiment of the present application, the unit area ratio of the spacer pattern per unit area of the first base layer is 5% or more and 17% or less, which means the ratio of the area on which the spacer pattern is formed to a specific unit area of the first base layer. For example, 2 The area where the pattern is formed is 10 mm 2 In this case, the area ratio of the spacer pattern can be defined as 10%.
[0022] In other words, when a specific unit area of the first base layer is defined as A and the area of the spacer pattern contained in the specific unit area of the first base layer is defined as B, the unit area ratio of the spacer pattern may satisfy the equation B / A×100=X%, and may mean the ratio of the area of the spacer pattern formed on the first base layer when the total area of the first base layer is defined as 100.
[0023] In one embodiment of the present application, the area ratio of the spacer pattern per unit area of the first base layer can satisfy 5% or more and 17% or less, preferably 6% or more and 17% or less, and more preferably 7% or more and 17% or less.
[0024] When the area ratio of the spacer pattern per unit area of the first base layer satisfies the above range, a variable transmittance device including the same will have excellent contrast and appearance.
[0025] In one embodiment of the present application, a patterned film is provided, wherein the spacer pattern is a regular pattern; or an irregular pattern.
[0026] In one embodiment of the present application, the spacer pattern may be a regular pattern.
[0027] In one embodiment of the present application, the spacer pattern may be an irregular pattern.
[0028] In one embodiment of the present application, the partition spacer is formed of a plurality of spacer dots and spacer lines connecting the spacer dots, and the spacer dots are used in the present application as a factor for adjusting the degree of regularity or irregularity. When a spacer pattern connected by the spacer lines is formed, the spacer lines and spacer dots are referred to as partition spacers.
[0029] Specifically, the method of manipulating the degree of disorder is as follows.
[0030] In one embodiment of the present application, the partition spacer has an irregular pattern, and the irregularity of the partition spacer is 50%, which means that the irregularity of the spacer dots used as an adjustment factor is 50%, and in the arrangement of each spacer dot, the spacer dots are randomly moved within a circular area having a radius (0.5 pitch) of 50% of the normal pitch of the selected spacer dot to have an irregular spacer pattern.
[0031] In other words, the irregularity of a spacer pattern is X%, which may mean that the irregularity of the spacer dots is X%, or that the irregularity satisfies X% by randomly moving the spacer dots within a circular area having a radius of X% (0.X pitch) of the normal pitch of the selected spacer dots.
[0032] Specifically, the method of manipulating the degree of order and disorder is as follows.
[0033] Spacer dots can be designed using a random coordinate generating program (CAD) in the following manner: First, 100 dots are arranged in a regular square (mesh) or hexagonal array at intervals (pitch) of 280 or 940 μm on a substrate layer with a total area of about 10 mm.
[0034] When the spacer dots are formed regularly as described above and then spacer dots are connected to form spacer lines to form a barrier rib spacer pattern, the irregularity of the spacer pattern can be defined as 0%, i.e., the spacer pattern has a regular pattern.
[0035] In the case of a square array, the irregularity of the spacer pattern is adjusted by setting a program so that individual spacer dots in a square formed by arbitrarily selecting four spacer dots move randomly within a circular region having a radius of 50% (0.5P) or 70% (0.7P) of the normal pitch (P) based on each spacer, and moving the individual spacer dots to form a spacer pattern arrangement having irregularity (50% or 70%). In the case of a hexagonal array, the only difference is that a regular hexagon formed by selecting six spacer dots is the configuration, and the remaining process is the same as for the square array.
[0036] The diameter of each spacer dot is set, and a spacer line is formed to connect the spacer dots, thereby completing a spacer pattern. The spacer pattern formed at this time may be a square pattern, a pentagonal pattern, or a hexagonal pattern, and the hexagonal array pattern may be a square pattern, a pentagonal pattern, or a heptagonal pattern.
[0037] 2 is a top view showing a case where the spacer dots have a regular pattern. Specifically, in the top view of a case where the spacer dots have a mesh pattern and a honeycomb pattern, the normal pitch and line width of each pattern can be confirmed.
[0038] 4 is a diagram showing a method for manipulating the 50% irregularity of a square spacer pattern. That is, in the case of a square array, a program is set so that individual spacer dots in a square formed by arbitrarily selecting four spacer dots are randomly moved within a circular region having a radius (0.5P) of 50% of the normal pitch (P) based on each spacer dot, and it can be confirmed that a spacer arrangement pattern having irregularity (50%) is formed by moving the individual spacer dots.
[0039] 5 is a diagram showing a pattern after manipulating the 50% irregularity of the square spacer pattern. Specifically, it can be seen that the square spacer pattern having 50% irregularity formed by the manipulation of FIG. 4 has a different pitch interval from that of FIG. 2.
[0040] In one embodiment of the present application, when the spacer pattern has an irregular pattern, the irregularity of the spacer pattern may be 50% or more, or less than 90%.
[0041] In another embodiment, the degree of disorder of the spacer pattern may be 50% or more and less than 90%, preferably 50% or more and less than 80%, more preferably 50% or more and less than 75%.
[0042] In one embodiment of the pattern film of the present application, the spacer pattern includes partition spacers and ball spacers, and the irregularity of the spacer pattern satisfies the above range, thereby expanding the pattern structure to include various patterns in one type of existing square (mesh) or hexagon (honeycomb) pattern and introducing irregularity, and a variable transmittance device including the same has the characteristics of excellent visibility with improved diffraction phenomenon and reduced diffuse reflection.
[0043] FIG. 1 shows a side view of a pattern film according to one embodiment of the present application, in which the pattern film has a spacer pattern on a substrate layer 10, and it can be seen that the spacer pattern includes partition spacers 20 and ball spacers 30, and that the ball spacers are embedded, partially embedded or in contact with at least one of the partition spacers.
[0044] In particular, FIG. 1 specifically shows the shape in which the ball spacers are included. The ball spacers embedded in the barrier spacer means that they are completely embedded inside, the partially embedded means that a portion of the ball spacer is embedded inside the barrier spacer and the other portion of the ball spacer is exposed to the outside, and the included in contact shape means that one side of the barrier spacer is in contact with one side of the ball spacer.
[0045] In one embodiment of the present application, there is provided a pattern film in which the average height (H) of the partition spacers is 2 μm or more and 100 μm or less, and the standard deviation of the height of the partition spacers is 0.05 μm or more and 0.5 μm or less.
[0046] In another embodiment, the average height (H) of the partition spacers may be 2 μm or more and 100 μm or less, preferably 5 μm or more and 90 μm or less, and more preferably 10 μm or more and 80 μm or less.
[0047] In still another embodiment, the standard deviation of the height of the partition spacers may be 0.05 μm or more and 0.5 μm or less, preferably 0.05 μm or more and 0.4 μm or less, and more preferably 0.05 μm or more and 0.3 μm or less.
[0048] In one embodiment of the present application, there is provided a pattern film in which the line width of the spacer pattern is 10 μm or more and 200 μm or less.
[0049] The line width of the spacer pattern may be, for example, 10 μm to 200 μm, and in other examples, may be 12 μm or more, 13 μm or more, 14 μm or more, 15 μm or more, 16 μm or more, 17 μm or more, 18 μm or more, 19 μm or more, 20 μm or more, 21 μm or more, 22 μm or more, 23 μm or more, 24 μm or more, 25 μm or more, or 26 μm or more, or may be 200 μm or less, 195 μm or less, 180 μm or less, 170 μm or less, 160 μm or less, 150 μm or less, 149 μm or less, 148 μm or less, 147 μm or less, or 146 μm or less.
[0050] In one embodiment of the present application, there is provided a pattern film, in which the pitch of the spacer pattern is 50 μm or more and 1,500 μm or less.
[0051] The pitch of the spacer pattern may be, for example, 50 μm or more and 1,500 μm or less, and in other examples, 50 μm or more, 100 μm or more, 150 μm or more, 200 μm or more, 250 μm or more, or 280 μm or more, or 1,500 μm or less, 1,400 μm or less, or 1,000 μm or less.
[0052] The pitch and line width of the spacer pattern can be appropriately selected within a range that does not impair the object of the present application.
[0053] In one embodiment of the present application, a pattern film is provided in which the line width (T) of the partition spacers and the average particle size (D) of the ball spacers satisfy the following formula 1. [Formula 1] 1.0≦T / D≦20
[0054] When the pattern film according to an embodiment of the present application satisfies the formula 1, the degree of hardening of the lower part of the barrier rib spacer is suitable, and the lower part of the spacer pattern can be prevented from being detached from the first base layer due to a stripper solution, a cleaning solution, or a developing pressure (1 bar or more) used in a subsequent process (development process). That is, when the formula 1 has a value less than 1.0, the degree of hardening of the lower part of the barrier rib spacer is insufficient, and the lower part of the spacer pattern can be detached from the first base layer due to a stripper solution, a cleaning solution, or a developing pressure (1 bar or more) used in a subsequent process (development process), resulting in a problem of the barrier rib spacer disappearing. When the formula 1 exceeds 20, an over-hardening phenomenon occurs in the crossing section (spacer dot section) of the barrier rib spacer, and hardening occurs in areas other than the barrier rib spacer, which can cause a problem of making it difficult to manufacture the barrier rib spacer by selective exposure / development.
[0055] In one embodiment of the present application, the line width (T) of the partition spacer can be appropriately adjusted in consideration of the transmittance variability of a transmittance variable device including the partition spacer later. Specifically, the line width (T) of the partition spacer may be 10 μm to 200 μm, and in other examples, may be 20 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, or 80 μm or more, or may be 190 μm or less, 180 μm or less, 170 μm or less, 160 μm or less, 150 μm or less, 140 μm or less, 130 μm or less, 120 μm or less, 110 μm or less, 100 μm or less, or 90 μm or less.
[0056] In the present application, the average particle size (D) of the ball spacers can be adjusted in consideration of the gap between the upper and lower substrates of a variable transmittance device including the ball spacers later. For example, the average particle size (D) of the ball spacers may be 1 μm to 15 μm, and in other examples, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, or 8 μm or more, or 15 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, 10 μm or less, or 9 μm or less.
[0057] In one embodiment of the present application, there is provided a pattern film in which the standard deviation of the particle size of the ball spacers is 0.8 μm or less.
[0058] In another embodiment, the standard deviation of the particle size of the ball spacers may be 0.8 μm or less, preferably 0.7 μm or less, more preferably 0.5 μm or less, and may be 0.05 μm or more.
[0059] In one embodiment of the present application, there is provided a pattern film, in which the optical density of the spacer pattern is 0.4 or more and 4 or less.
[0060] The optical density can be calculated by measuring the transmittance (unit: %) of the spacer pattern and then substituting the measured transmittance into a formula for optical density (optical density=-log10(T), where T is the transmittance).
[0061] In another embodiment, the optical density of the spacer pattern can satisfy 0.4 to 4.0, preferably 0.5 to 3.5, and more preferably 1.0 to 3.0.
[0062] In a transmittance variable device capable of adjusting the transmittance, color, or reflectance of light, the region where the spacer pattern exists becomes an optically inactive region, and the pattern film according to the present application satisfies the above optical density range, thereby controlling light leakage and realizing manufacturing stability of the spacer pattern, and thus ensuring uniform optical performance when applied to a transmittance variable device in the future. That is, if the optical density is below the above range, light leakage may occur as it passes through the inside of the spacer pattern, which is an optically inactive region, during device operation, and if the optical density exceeds the above range, the content of black particles (such as carbon black) that realize low transmittance (0.01%) increases, which may hinder UV curing of the polymer resin, resulting in a problem of defective pattern manufacturing.
[0063] In one embodiment of the present application, the first substrate layer may be any substrate layer used as a substrate in the configuration of a known optical device such as an LCD (Liquid Crystal Display) without any particular limitation. For example, the first substrate layer may be an inorganic substrate layer or an organic substrate layer. Examples of the inorganic substrate layer include a glass substrate layer, and examples of the organic substrate layer include various plastic films. Examples of plastic films include, but are not limited to, TAC (triacetyl cellulose) film; COP (cyclo olefin copolymer) films such as norbornene derivatives; acrylic films such as PMMA (poly(methyl methacrylate); PC (polycarbonate) film; polyolefin films such as PE (polyethylene) or PP (polypropylene); PVA (polyvinyl alcohol) film; DAC (diacetyl cellulose) film; PAC (Polyacrylate) film; PES (poly ether sulfone) film; PEEK (polyetheretherketon) film; PPS (polyphenylsulfone) film, PEI (polyetherimide) film; PEN (polyethylenemaphthalate) film; PET (polyethyleneterephtalate) film; PI (polyimide) film; PSF (polysulfone) film, and PAR (polyarylate) film.
[0064] In one example, the first substrate layer may be a so-called flexible substrate layer. The specific type of the flexible substrate layer is not particularly limited, and among the substrate layers described above, mainly plastic films and very thin inorganic substrates such as thin glass can be used as the flexible substrate layer.
[0065] The thickness of the first base layer is not particularly limited and an appropriate range can be selected depending on the application. Specifically, the thickness can satisfy the range of 1 μm or more and 1,000 μm or less, preferably 10 μm or more and 900 μm or less, and more preferably 30 μm or more and 500 μm or less.
[0066] In one embodiment of the present application, other elements required for driving the variable transmittance device may be additionally included between the first base layer and the spacer pattern. Such elements are variously known, and representatively include an electrode layer.
[0067] That is, in one embodiment of the present application, the patterned film may additionally include an electrode layer between the base layer and the spacer pattern.
[0068] Known materials can be used for the electrode layer. For example, the electrode layer can include a metal alloy, an electrically conductive compound, or a mixture of two or more of the above. Examples of such materials include metals such as gold, CuI, ITO (indium tin oxide), IZO (indium zinc oxide), ZTO (zinc tin oxide), zinc oxide doped with aluminum or indium, magnesium indium oxide, nickel tungsten oxide, ZnO, SnO2, or In2O3, and other oxide materials, metal nitrides such as gallium nitride, metal selenides such as zinc selenide, and metal sulfides such as zinc sulfide. The transparent hole injection electrode layer can also be formed using a laminate of a metal thin film such as Au, Ag, or Cu and a highly refractive transparent material such as ZnS, TiO2, or ITO.
[0069] The electrode layer is formed by any means such as vapor deposition, sputtering, chemical vapor deposition, or electrochemical means. The electrode layer can be patterned by a known method without any particular limitation, for example, by a known process using photolithography or a shadow mask.
[0070] In one embodiment of the present application, there is provided a variable transmittance device comprising a pattern film according to the present application and a second substrate arranged opposite the pattern film and maintaining a distance from the pattern film by the spacer pattern of the pattern film.
[0071] The variable transmittance device can be applied to various applications. Examples of applications to which the variable transmittance device can be applied include smart windows, window protection films, flexible display elements, active retarders or viewing angle adjustment films for 3D image display, windows or sunroofs for openings in enclosed spaces including buildings, containers, or vehicles, eyewear, and light shields for building fixtures and organic light emitting devices (OLEDs). The scope of eyewear includes all eyewear formed to allow a viewer to view the outside through a lens, such as general glasses, sunglasses, sports goggles or helmets, or wearable devices such as devices for experiencing virtual reality or augmented reality.
[0072] In one example, the variable transparency device may be a vehicle sunroof by itself, for example, in an automobile including a body having at least one opening, the variable transparency device or vehicle sunroof may be installed in the opening.
[0073] The sunroof may be a general term for a device that is a fixed or movable (venting or sliding) opening in the roof of a vehicle and functions to allow light or fresh air to flow into the interior of the vehicle. In the present application, the operation method of the sunroof is not particularly limited, and for example, the sunroof may be operated manually or driven by a motor, and the shape, size, or style of the sunroof may be appropriately selected depending on the intended use. For example, the sunroof may be exemplified by a pop-up type sunroof, a spoiler (tile & slide) type sunroof, an in-built type sunroof, a folding type sunroof, a top-mounted type sunroof, a panoramic roof system type sunroof, a removable roof panel (T-tops or targa roofts) type sunroof, or a solar type sunroof, depending on the operation method, but is not limited thereto.
[0074] An exemplary sunroof of the present application may include the variable transparency device of the present application, and in this case, the specific matters relating to the variable transparency device are similarly applicable to the contents described in the variable transparency device section.
[0075] In one embodiment of the present application, a variable transmittance device is provided, wherein the second substrate includes a second base layer, a transparent layer formed on the second base layer, and an adhesive layer provided on the surface of the transparent layer opposite the surface that contacts the second base layer, and the adhesive layer contacts the spacer pattern side.
[0076] In addition, in one embodiment of the present application, there is provided a variable transmittance device, further comprising an alignment film provided to cover the spacer pattern of the pattern film.
[0077] In one embodiment of the present application, there is provided a variable transmittance device further including a light modulating layer provided at a position where a distance from the pattern film is maintained by the spacer pattern.
[0078] FIG. 3 is a diagram showing a layered structure of a variable transmittance device according to an embodiment of the present application.
[0079] Specifically, it can be seen that the film includes a spacer pattern including partition wall spacers 20 and ball spacers 30 on a first substrate layer 10, and an alignment film 40 formed to cover the top of the spacer pattern, and that the film includes a second laminate consisting of a second substrate layer 80 / transparent layer 70 / adhesive layer 60, with the adhesive layer having a structure in contact with the spacer pattern side, and a light modulation layer 50 provided at a position where a distance from the pattern film is maintained by the spacer pattern.
[0080] The light modulation layer of the present application may refer to a layer containing at least a liquid crystal compound, and the alignment state of the liquid crystal compound may be controlled by application of an external signal. As the liquid crystal compound, any type of liquid crystal compound may be used as long as the alignment direction of the liquid crystal compound can be changed by application of an external signal. As the liquid crystal compound, for example, a nematic liquid crystal compound, a smectic liquid crystal compound, or a cholesteric liquid crystal compound may be used. In addition, the liquid crystal compound may be, for example, a compound having no polymerizable group or crosslinkable group so that the alignment direction of the liquid crystal compound can be changed by application of an external signal.
[0081] The light modulating layer of the present application may further include a dichroic dye in addition to the liquid crystal compound. In this specification, the term "dye" may mean a substance capable of intensively absorbing and / or transforming light within at least a part or the entire range of the visible light region, for example, a wavelength range of 400 nm to 700 nm, and the term "dichroic dye" may mean a substance capable of anisotropic absorption of light within at least a part or the entire range of the visible light region. As such dyes, for example, azo dyes or anthraquinone dyes are well known, but are not limited thereto.
[0082] In one example, the light modulation layer may be a liquid crystal layer containing a liquid crystal compound and a dichroic dye, and may be a so-called guest host liquid crystal layer. The term "GHLC layer" may refer to a functional layer in which dichroic dyes are aligned together by the alignment of liquid crystals, and which exhibits anisotropic light absorption characteristics in the alignment direction of the dichroic dyes and in a direction perpendicular to the alignment direction. For example, a dichroic dye is a material whose light absorption rate differs depending on the polarization direction, and if it has a high absorption rate for light polarized in the long axis direction, it may be called a p-type dye, and if it has a high absorption rate for light polarized in the short axis direction, it may be called an n-type dye. In one example, when a p-type dye is used, polarized light vibrating in the long axis direction of the dye is absorbed, and polarized light vibrating in the short axis direction of the dye is less absorbed and can be transmitted. Hereinafter, unless otherwise specified, it is assumed that the dichroic dye is a p-type dye.
[0083] The present inventors have confirmed that light leakage during side observation that may occur in a transmittance variable device can be prevented by incorporating a dichroic dye together with a liquid crystal compound in the light modulation layer as described above. The orientation of the dichroic dye in the guest-host liquid crystal layer follows the orientation of the liquid crystal compound. Therefore, for example, in the case where the transmittance variable device is a device designed to realize low transmittance when the liquid crystal compound is vertically aligned, the dichroic dye is also vertically aligned or in a state equivalent thereto when the liquid crystal compound is vertically aligned. The dichroic dye aligned in such a vertical or equivalent state can absorb light leaking during side observation. In particular, by introducing this method, it is possible to prevent side light leakage without introducing a separate compensation structure, and even when the polymer film substrate is not an isotropic substrate, it is possible to prevent side light leakage without a complicated design.
[0084] The effect of preventing side light leakage by the dichroic dye can be further improved by the contents of the variable transmittance device of the present application, which will be described later. That is, in a light modulation layer including a liquid crystal compound and a dichroic dye, the orientation of the dichroic dye follows the orientation of the liquid crystal compound, and at this time, the orientation of the liquid crystal compound is determined by the type of liquid crystal alignment film. The inventors have confirmed that the orientation of the liquid crystal compound formed by an adhesive (adhesive) having a vertical alignment force, as described later, is an orientation that allows the dichroic dye, which follows the orientation, to effectively block light leaking to the side. Therefore, the effect of preventing side light leakage by the dichroic dye can be further maximized by the contents of the present application, which will be described later.
[0085] The liquid crystal compound included in the light modulating layer may be in a vertically aligned state in the absence of an external action, i.e., in an initial state or normal state. In this specification, the term "external action" refers to any type of action that can change the orientation or alignment of the liquid crystal compound, and a representative example is application of a voltage. The alignment direction of the liquid crystal compound in the vertically aligned state may be changed by an external action, and the liquid crystal compound may return to the vertically aligned state when the external action is removed.
[0086] In the application of the variable transmittance device, the retardation (Rc) can be appropriately determined depending on the mode or structure to be realized. For example, the liquid crystal layer containing the liquid crystal compound existing in the vertically aligned state has an in-plane retardation (Rc) calculated by the following formula 1 in the absence of external force. in ) is 30 nm or less, and the retardation in the thickness direction (R th ) can be in the range of 500 nm or more. A retardation in such a range is appropriate for realizing, for example, a normal transmission mode element. [Formula 1] R in =d×(nx-ny) [Formula 2] R th =d×(nz-ny) R in is the in-plane retardation, and R this the phase difference in the thickness direction, d is the thickness of the light modulation layer, nx is the refractive index in the slow axis direction on the surface of the light modulation layer, ny is the refractive index in the fast axis direction on the surface of the light modulation layer, and nz is the refractive index in the thickness direction of the light modulation layer.
[0087] The variable transmittance device may exhibit a transparent mode in the absence of an external action, and may be converted into various modes other than the transparent mode by an external action. The light transmittance of the variable transmittance device in the absence of an external action may be appropriately adjusted according to the application of the variable transmittance device within a range that does not impair the object of the present application. The method of adjusting the light transmittance of the variable transmittance device is not particularly limited, and may be, for example, by adjusting the content of a dichroic dye described below.
[0088] The dichroic dye contained in the light modulation layer can absorb at least a wavelength in the visible light region, for example, within a range of about 400 nm to 700 nm. As long as such absorption characteristics are ensured, one type of dichroic dye may be used, or a mixture of two or more types may be used.
[0089] In one embodiment of the present application, the type of the dichroic dye is not particularly limited, and for example, any type of dye known to have the above-mentioned characteristics and the ability to be aligned by the alignment of a liquid crystal compound can be used. As the dichroic dye, for example, a black dye or a color dye can be used.
[0090] The ratio of the dichroic dye contained in the light modulation layer may be, for example, 5% by weight or less. The ratio of the dichroic dye is the ratio of the dichroic dye to the weight of all components contained in the light modulation layer. For example, if the light modulation layer includes a liquid crystal compound, a dichroic dye, and a chiral dopant, the percentage of the dichroic dye to the total weight of the three components is the ratio of the dichroic dye. If the ratio of the dichroic dye is too high, when the dichroic dye follows the horizontal alignment of the liquid crystal compound, it may absorb too much light from the front, which is not the effect intended in this application. That is, it is appropriate that the ratio of the dichroic dye is controlled so that the side light leakage can be effectively prevented when the dye follows the vertical alignment of the liquid crystal compound, while the front light can be absorbed to a minimum when the dye follows the horizontal alignment of the liquid crystal compound. In other examples, the ratio of the dichroic dye may be, but is not limited to, 4 wt % or less, 3 wt % or less, 2 wt % or less, or 1 wt % or less, or 0.1 wt % or more, 0.2 wt % or more, 0.3 wt % or more, or 0.4 wt % or more.
[0091] By including a dichroic dye in the light modulation layer in the above range, the present application can provide a variable transmittance device that has excellent viewing angle compensation effect by controlling the light leakage phenomenon on the sides while exhibiting a transmittance in the transmission mode of the variable transmittance device in the range described below.
[0092] The present application may relate to a variable transmittance device designed to adjust the alignment of liquid crystal compounds in the light modulating layer so that the initial alignment is vertical and the vertical alignment state can be changed to a horizontal alignment state by application of an external signal, the initial alignment being the alignment state when no external signal is applied to the light modulating layer.
[0093] In this specification, the term "vertical alignment" refers to a state in which the director of the light modulation layer or the director of the liquid crystal compound in the light modulation layer is aligned almost perpendicular to the plane of the light modulation layer, and for example, the angle between the z-axis, which is the normal to the reference plane of the light modulation layer, and the director may be within a range of about 80° to 100° or 85° to 95°, or may be about 90°. Also, the term "horizontal alignment" refers to a state in which the director of the light modulation layer or the director of the liquid crystal compound in the light modulation layer is aligned almost parallel to the reference plane of the light modulation layer, and for example, the angle between the director and the reference plane of the light modulation layer may be within a range of about 0° to 10° or about 0° to 5°, or may be about 0°.
[0094] In this specification, the term director of the light modulation layer or director of the liquid crystal compound may refer to the optical axis or slow axis of the light modulation layer. For example, the optical axis or slow axis may refer to the long axis direction when the liquid crystal molecule is rod-shaped, may refer to the axis normal to the disc plane when the liquid crystal molecule is discotic, and may refer to the vector sum of the directors of the liquid crystal compounds when the light modulation layer contains a plurality of liquid crystal compounds with different directors.
[0095] In one example, the light modulation layer is designed to realize a twisted alignment mode. In this specification, the term twisted alignment mode may refer to a helical structure in which the directors of the liquid crystal compounds are aligned in layers while twisting along a virtual helical axis. The twisted alignment mode may be realized by the above-mentioned vertical or horizontal alignment mode. For example, the vertical twisted alignment mode may refer to a state in which individual liquid crystal compounds are aligned vertically and twisted along a helical axis to form layers, and the horizontal twisted alignment mode may refer to a state in which individual liquid crystal compounds are aligned horizontally and twisted along a helical axis to form layers.
[0096] In the twisted alignment mode, the ratio (d / p) of the thickness (d) of the light modulating layer to the pitch (p) may be, for example, 1 or less. If the ratio (d / p) exceeds 1, problems such as finger domains may occur, so it is adjusted to be within the above range as much as possible. In other examples, the ratio (d / p) may be about 0.95 or less, about 0.9 or less, about 0.85 or less, about 0.8 or less, about 0.75 or less, about 0.7 or less, about 0.65 or less, about 0.6 or less, about 0.55 or less, about 0.5 or less, or about 0.45 or less, or about 0.1 or more, about 1.15 or more, about 0.2 or more, about 0.25 or more, about 0.3 or more, or about 0.35 or more. The thickness (d) of the light modulating layer may have the same meaning as the cell gap in the transmittance variable device.
[0097] The pitch (p) of the light modulation layer in the twisted orientation mode can be measured using a measurement method that uses a wedge cell, specifically, using the method described in "Simple method for accurate measurements of the cholesteric pitch using a stripe-wedge Grandjean-Cano cell" by D. Podolskyy et al. (Liquid Crystals, Vol. 35, No. 7, July 8, 2008, 789-791).
[0098] The alignment of the liquid crystal compound formed by the above-mentioned ratio of thickness (d) and pitch (p) and the alignment of the dichroic dye that follows it can effectively absorb light leaking from the sides in vertical alignment and minimize absorption of front light in horizontal alignment.
[0099] In order to enable the light modulating layer to realize a twist mode, the light modulating layer can additionally include a so-called chiral dopant, i.e., the light modulating layer can additionally include a chiral dopant together with a liquid crystal compound and a dichroic dye.
[0100] The chiral dopant contained in the light modulation layer can be used without any particular limitation as long as it can induce the desired twisting without impairing the liquid crystal property, for example, nematic regularity. The chiral dopant for inducing the rotation of the liquid crystal molecules must at least have chirality in its molecular structure. Examples of the chiral dopant include a compound having one or more asymmetric carbons, a compound having an asymmetric point on a heteroatom such as chiral amine or chiral sulfoxide, or a compound having an axially asymmetric, optically active site such as cumulene or binaphthol. The chiral dopant may be, for example, a low molecular weight compound having a molecular weight of 1,500 or less. As the chiral dopant, commercially available chiral nematic liquid crystals, for example, chiral dopant liquid crystal S811 available from Merck or LC756 from BASF, can be used.
[0101] The ratio of the chiral dopant to be applied is not particularly limited as long as the desired ratio (d / p) can be achieved. In general, the content (wt%) of the chiral dopant is calculated by the formula 100 / (HTP (Helixcal Twisting power)×pitch (nm), and is selected at an appropriate ratio taking into account the desired pitch (p).
[0102] The light modulating layer may include a liquid crystal compound having a negative dielectric anisotropy, or the light modulating layer may exhibit the above-mentioned dielectric anisotropy. The absolute value of the dielectric anisotropy may be appropriately selected in consideration of the object of the present application. The term "dielectric anisotropy (Δλ)" may mean the difference (ε / / -ε⊥) between the horizontal dielectric constant (ε / / ) and the vertical dielectric constant (ε⊥). In this specification, the term horizontal dielectric constant (ε / / ) means a dielectric constant value measured along the direction of an electric field in a state where a voltage is applied so that the directors of liquid crystal molecules and the direction of the electric field caused by the applied voltage are substantially horizontal, and the term vertical dielectric constant (ε⊥) means a dielectric constant value measured along the direction of an electric field in a state where a voltage is applied so that the directors of liquid crystal molecules and the direction of the electric field caused by the applied voltage are substantially perpendicular to each other.
[0103] The liquid crystal layer may include a liquid crystal compound having a refractive index anisotropy (n△) in the range of about 0.04 to 0.15, or the liquid crystal layer may exhibit the above-mentioned refractive index anisotropy. The refractive index anisotropy (n△) in the present application is the difference (ne-no) between the extraordinary refractive index (ne, extraordinary refractive index) and the ordinary refractive index (no, ordinary refractive index), and may be confirmed using an Abbe refractometer, the specific method of which is disclosed in the following examples. In other examples, the refractive index anisotropy (n△) may be about 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, or 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, or 0.09 or more.
[0104] The thickness of the light modulation layer of the present application can be appropriately selected in consideration of the purpose of the present application. In one example, the thickness of the light modulation layer may be about 15 μm or less. By controlling the thickness in this manner, a device with a large difference in transmittance between the transmission mode and the blocking mode, that is, a device with excellent transmittance variable characteristics, can be realized. In other examples, the thickness may be about 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, 10 μm or less, 9 μm or less, or 8 μm or less, or 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, or 8 μm or more, but is not limited thereto.
[0105] In one embodiment of the present application, the transparent layer may be a transparent conductive layer, which is formed by depositing, for example, a conductive polymer, a conductive metal, a conductive nanowire, or a metal oxide such as ITO (Indium Tin Oxide), etc. In addition, various materials and formation methods for forming a transparent conductive layer are known, and these may be used without limitation.
[0106] The adhesive layer of the present application provides a variable transmission device that includes an adhesive or pressure sensitive adhesive with a vertical orientation force.
[0107] As used herein, the term "adhesive or pressure sensitive adhesive having vertical alignment force" can refer to a layer containing a vertically aligning adhesive that imparts vertical alignment force to the material present in the light modulating layer while at the same time having adhesive force capable of adhering a first laminate and a second laminate.
[0108] In this specification, the term adhesive layer having vertical alignment power may refer to a material that simultaneously has vertical alignment power and adhesive or cohesive power to liquid crystal molecules.
[0109] In the present application, the adhesive layer having vertical alignment power may be, for example, a silicone adhesive or pressure-sensitive adhesive. The silicone adhesive or pressure-sensitive adhesive may be a cured product of a composition containing a curable silicone compound. The type of the curable silicone compound is not particularly limited, and may be, for example, a heat-curable silicone compound or an ultraviolet-curable silicone compound.
[0110] In one embodiment of the present application, the curable silicone compound can include, as an addition-curable silicone compound, (1) an organopolysiloxane containing two or more alkenyl groups in the molecule, and (2) an organopolysiloxane containing two or more silicon-bonded hydrogen atoms in the molecule. Such silicone compounds can form a cured product by addition reaction in the presence of a catalyst described below, for example.
[0111] In the above, (1) organopolysiloxane can contain at least two alkenyl groups in one molecule as the main component constituting the silicone cured product. At this time, specific examples of the alkenyl group include vinyl group, allyl group, butenyl group, pentenyl group, hexenyl group, heptenyl group, etc., among which vinyl group is preferred, but is not limited thereto. In the (1) organopolysiloxane, the bonding position of the above-mentioned alkenyl group is not particularly limited. For example, the alkenyl group may be bonded to the terminal of the molecular chain and / or to the side chain of the molecular chain. In the (1) organopolysiloxane, examples of the types of substituents that may be contained other than the alkenyl groups include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, and heptyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl and phenethyl; and halogen-substituted alkyl groups such as chloromethyl, 3-chloropropyl, and 3,3,3-trifluoropropyl. Of these, methyl and phenyl groups are preferred, but the examples are not limited thereto.
[0112] The molecular structure of the (1) organopolysiloxane is not particularly limited, and may have any shape, such as linear, branched, cyclic, network, or partially branched linear. In the present application, it is particularly preferred to have a linear molecular structure among the above molecular structures, but this is not limited thereto. On the other hand, in the present invention, from the viewpoint of hardness and refractive index of the cured product, it is preferred to use an organopolysiloxane containing an aromatic group such as an aryl group or an aralkyl group in the molecular structure as the (1) organopolysiloxane, but this is not necessarily limited thereto.
[0113] More specific examples of the organopolysiloxane (1) that can be used in the present application include dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxane groups, methylvinylpolysiloxanes capped at both molecular chain terminals with trimethylsiloxane groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxane groups, dimethylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxane groups, methylvinylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxane groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxane groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxane groups, R 1 2SiO 1 / 2 The siloxane unit represented by R 1 2R 2 SiO 1 / 2 The siloxane unit represented by and SiO 4 / 2 and an organopolysiloxane copolymer containing a siloxane unit represented by R 1 2R 2 SiO 1 / 2 The siloxane unit represented by and SiO 4 / 2 and an organopolysiloxane copolymer containing a siloxane unit represented by R 1 R 2 SiO 2 / 2 The siloxane unit represented by R 1SiO 3 / 2 Siloxane units represented by R 2 SiO 3 / 2 and mixtures of two or more of the above. 1 is a hydrocarbon group other than an alkenyl group, specifically, an alkyl group such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, or a heptyl group; an aryl group such as a phenyl group, a tolyl group, a xylyl group, or a naphthyl group; an aralkyl group such as a benzyl group or a phenethyl group; or a halogen-substituted alkyl group such as a chloromethyl group, a 3-chloropropyl group, or a 3,3,3-trifluoropropyl group. 2 is an alkenyl group, and specifically may be a vinyl group, an allyl group, a butenyl group, a pentenyl group, a hexenyl group, a heptenyl group, or the like.
[0114] In one embodiment of the present invention, the (1) organopolysiloxane may have a viscosity of 50 to 500,000 CP (centipoise), preferably 400 to 100,000 CP, at 25° C. If the viscosity is less than 50 CP, the mechanical strength of the cured product of the silicone compound may decrease, and if it exceeds 500,000 CP, handling or workability may decrease.
[0115] In the addition curing silicone compound, the (2) organopolysiloxane can play a role in crosslinking the (1) organopolysiloxane. In the (2) organopolysiloxane, the bond position of the hydrogen atom is not particularly limited, and may be bonded to, for example, the end of the molecular chain and / or the side chain. In the (2) organopolysiloxane, the type of the substituent that may be contained other than the silicon-bonded hydrogen atom is not particularly limited, and examples thereof include alkyl groups, aryl groups, aralkyl groups, and halogen-substituted alkyl groups, as mentioned in the (1) organopolysiloxane, and among these, methyl groups and phenyl groups are preferred, but are not limited thereto.
[0116] On the other hand, the molecular structure of (2) organopolysiloxane is not particularly limited, and may have any shape, for example, linear, branched, cyclic, network, partially branched linear, etc. In the present invention, among the above molecular structures, it is particularly preferable to have a linear molecular structure, but this is not limiting.
[0117] More specific examples of the organopolysiloxane (2) that can be used in the present invention include methylhydrogenpolysiloxanes capped with trimethylsiloxane groups at both molecular chain terminals, dimethylsiloxane-methylhydrogen copolymers capped with trimethylsiloxane groups at both molecular chain terminals, dimethylsiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymers capped with trimethylsiloxane groups at both molecular chain terminals, dimethylpolysiloxanes capped with dimethylhydrogensiloxane groups at both molecular chain terminals, dimethylsiloxane-methylphenylsiloxane copolymers capped with dimethylhydrogensiloxane groups at both molecular chain terminals, methylphenylpolysiloxanes capped with dimethylhydrogensiloxane groups at both molecular chain terminals, R 1 3SiO 1 / 2 The siloxane unit represented by R 1 2HSiO 1 / 2 The siloxane unit represented by the formula 4 / 2 and an organopolysiloxane copolymer containing a siloxane unit represented by R 1 2HSiO 1 / 2 The siloxane unit represented by the formula 4 / 2 and an organopolysiloxane copolymer containing a siloxane unit represented by R 1 HSiO 2 / 2 The siloxane unit represented by R 1 SiO 3 / 2 Siloxane units represented by HSiO 3 / 2 and mixtures of two or more of the above. 1is a hydrocarbon group other than an alkenyl group, and specifically may be an alkyl group such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, or a heptyl group; an aryl group such as a phenyl group, a tolyl group, a xylyl group, or a naphthyl group; an aralkyl group such as a benzyl group or a phenethyl group; or a halogen-substituted alkyl group such as a chloromethyl group, a 3-chloropropyl group, or a 3,3,3-trifluoropropyl group.
[0118] In the present application, for example, the (2) organopolysiloxane may have a viscosity of 1 to 500,000 CP (centipoise), preferably 5 to 100,000 CP, at 25° C. If the viscosity is less than 1 CP, the mechanical strength of the cured product of the silicone compound may decrease, and if it exceeds 500,000 CP, the handleability or workability may decrease.
[0119] In the present application, the content of the (2) organopolysiloxane is not particularly limited as long as it is contained to an extent that suitable curing is performed. For example, the (2) organopolysiloxane is contained in an amount such that the number of silicon-bonded hydrogen atoms is 0.5 to 10 per one alkenyl group contained in the (1) organopolysiloxane described above. If the number of silicon-bonded hydrogen atoms is less than 0.5, the curable silicone compound may be insufficiently cured, and if the number exceeds 10, the heat resistance of the cured product may be reduced. On the other hand, in the present invention, from the viewpoint of the hardness and refractive index of the cured product, it is preferable to use, as the (2) organopolysiloxane, an (2) organopolysiloxane containing an aromatic group such as an aryl group or an aralkyl group in the molecular structure, but this is not necessarily limited thereto.
[0120] In the present application, the addition curing silicone compound may further include platinum or a platinum compound as a catalyst for curing.Specific examples of such platinum or platinum compounds include platinum fine powder, platinum black, platinum-supported silica fine powder, platinum-supported activated carbon, chloroplatinic acid, platinum tetrachloride, alcohol solution of chloroplatinic acid, complexes of platinum and olefins, complexes of platinum and alkenylsiloxane such as 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, and thermoplastic resin fine powders (polystyrene resin, nylon resin, polycarbonate resin, silicone resin, etc.) containing these platinum or platinum compounds and having a particle size of less than 10 μm, but are not limited thereto.
[0121] The content of the catalyst in the addition curable silicone compound of the present invention is not particularly limited, and is, for example, 0.1 to 500 ppm by weight, preferably 1 to 50 ppm by weight, based on the total compound. If the content of the catalyst is less than 0.1 ppm, the curability of the composition may be reduced, and if it exceeds 500 ppm, the economical efficiency may be reduced.
[0122] In the present application, the addition curing silicone compound may additionally contain, from the viewpoint of improving its storage stability, handling and workability, alkyne alcohols such as 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, phenylbutynol, etc.; enyne compounds such as 3-methyl-3-penten-1-yne, 3,5-dimethyl-3-hexen-1-yne, etc.; curing inhibitors such as 1,2,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, 1,3,5,7-tetramethyl-1,3,5,7-trahexenylcyclotetrasiloxane, benzotriazole, etc. The content of the curing inhibitor can be appropriately selected within a range that does not impede the object of the invention, and is, for example, contained in a range of 10 ppm to 50,000 ppm based on weight.
[0123] In the present application, the silicone compound can include, as a condensation curable silicone compound, for example, (a) an alkoxy group-containing siloxane polymer; and (b) a hydroxyl group-containing siloxane polymer.
[0124] The (a) siloxane polymer that can be used in the present invention may be, for example, a compound represented by the following chemical formula 1. [Chemical formula 1] R1 a R2 b SiO c (OR3) d In the above formula, R1 and R2 each independently represent a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group, R3 represents an alkyl group, and when there are multiple R1, R2, and R3, they may be the same or different from each other, a and b each independently represent a number greater than 0 and less than 1, a+b represents a number greater than 0 and less than 2, c represents a number greater than 0 and less than 2, d represents a number greater than 0 and less than 4, and (a+b+c)×2+d is 4.
[0125] In the present invention, the siloxane polymer represented by the above chemical formula 1 may have a polystyrene-equivalent weight average molecular weight of 1,000 to 100,000, preferably 1,000 to 80,000, and more preferably 1,500 to 70,000, as measured by gel permeation chromatography. (a) When the weight average molecular weight of the siloxane polymer is within the above range, defects such as cracks do not occur during formation of a silicone cured product, and a good cured product can be obtained.
[0126] In the definition of Chemical Formula 1, the monovalent hydrocarbon may be, for example, an alkyl group having 1 to 8 carbon atoms, a phenyl group, a benzyl group, or a tolyl group, and in this case, the alkyl group having 1 to 8 carbon atoms may be, for example, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, or an octyl group. In addition, in the definition of Chemical Formula 1, the monovalent hydrocarbon group may be substituted with a known substituent such as, for example, a halogen, an amino group, a mercapto group, an isocyanate group, a glycidyl group, a glycidoxy group, or a ureido group. In addition, in the definition of Chemical Formula 1, examples of the alkyl group of R3 include a methyl group, an ethyl group, a propyl group, an isopropyl group, or a butyl group. Among such alkyl groups, a methyl group or an ethyl group is preferable, but is not limited thereto.
[0127] In the present invention, it is preferable to use a branched or tertiary crosslinked siloxane polymer among the polymers of Chemical Formula 1. In addition, the siloxane polymer (a) may have residual hydroxyl groups within a range that does not impair the object of the present invention, specifically, within a range that does not inhibit the dealcoholization reaction.
[0128] The above-mentioned (a) siloxane polymer can be produced, for example, by hydrolysis and condensation of polyfunctional alkoxysilane or polyfunctional chlorosilane. An average technician in this field can easily select an appropriate polyfunctional alkoxysilane or chlorosilane according to the desired (a) siloxane polymer, and can easily control the conditions of the hydrolysis and condensation reaction using it. Meanwhile, when producing the above-mentioned (a) siloxane polymer, an appropriate monofunctional alkoxysilane can also be used in combination depending on the purpose.
[0129] As the (a) siloxane polymer, for example, commercially available organosiloxane polymers such as X40-9220 or X40-9225 from Shin-Etsu Silicone Co., Ltd., XR31-B1410, XR31-B0270, or XR31-B2733 from GE Toray Silicone Co., Ltd. can be used. On the other hand, in the present invention, from the viewpoint of hardness and refractive index of the cured product, it is preferable to use an (a) organopolysiloxane containing an aromatic group such as an aryl group or an aralkyl group in the molecular structure as the (a) organopolysiloxane, but this is not necessarily limited thereto. On the other hand, as the (b) hydroxyl group-containing siloxane polymer contained in the condensation curing type silicone compound, for example, a compound represented by the following chemical formula 2 can be used. [Chemical formula 2] [ka] In the above chemical formula 2, R4 and R5 each independently represent hydrogen; or a substituted or unsubstituted monovalent hydrocarbon group, and when there are multiple R4 and multiple R5, they may be the same or different, and n represents an integer of 5 to 2,000.
[0130] In the definition of Chemical Formula 2, specific examples of the monovalent hydrocarbon group include the same hydrocarbon groups as those in Chemical Formula 1 described above.
[0131] In the present invention, the siloxane polymer of formula 2 may have a polystyrene-equivalent weight average molecular weight of 500 to 100,000, preferably 1,000 to 80,000, and more preferably 1,500 to 70,000, as measured by gel permeation chromatography. (b) When the weight average molecular weight of the siloxane polymer is within the above range, defects such as cracks do not occur during the formation of a silicone cured product, and a good cured product can be obtained.
[0132] The (b) siloxane polymer can be produced, for example, by hydrolysis and condensation of dialkoxysilane and / or dichlorosilane. An average technician in this field can easily select an appropriate dialkoxysilane or dichlorosilane depending on the desired (b) siloxane polymer, and can easily control the conditions of the hydrolysis and condensation reaction using the dialkoxysilane or dichlorosilane. As the (b) siloxane polymer, for example, commercially available bifunctional organosiloxane polymers such as XC96-723, YF-3800, and YF-3804 of GE Toray Silicone can be used. On the other hand, in the present invention, from the viewpoint of hardness and refractive index of the cured product, it is preferable to use, as the (1) organopolysiloxane, an (1) organopolysiloxane containing an aromatic group such as an aryl group or an aralkyl group in the molecular structure, but this is not necessarily limited thereto.
[0133] The type of the adhesive layer having the vertical alignment force is not particularly limited and can be appropriately selected according to the intended use. For example, a solid adhesive or pressure-sensitive adhesive, a semi-solid adhesive or pressure-sensitive adhesive, an elastic adhesive or pressure-sensitive adhesive, or a liquid adhesive or pressure-sensitive adhesive can be appropriately selected and used. The solid adhesive or pressure-sensitive adhesive, the semi-solid adhesive or pressure-sensitive adhesive, and the elastic adhesive or pressure-sensitive adhesive are so-called pressure-sensitive adhesives or pressure-sensitive adhesives (PSA; Pressure Sensitive Adhesives) and can be cured before the objects to be bonded or adhered are bonded together. The liquid adhesive or pressure-sensitive adhesive is so-called optically clear resin (OCR; Optical Clear Resin) and can be cured after the objects to be bonded or adhered are bonded together. In the present application, for example, a polydimethyl siloxane adhesive or a polymethylvinyl siloxane adhesive can be used as a PSA type adhesive or pressure-sensitive adhesive having vertical alignment force, and an alkoxy silicone adhesive or pressure-sensitive adhesive can be used as an OCR type adhesive having vertical alignment force, but is not limited thereto.
[0134] In the above-described configuration, by including an adhesive layer having the above-described properties, it is possible to provide a variable transmittance device that has excellent adhesive or cohesive strength, while controlling light leakage, particularly in blocking mode, and exhibits excellent optical properties.
[0135] In one embodiment of the present application, the adhesive or pressure sensitive adhesive having a vertical alignment force may contain functional nanoparticles.
[0136] In the above, the term "functional nanoparticles" refers to nano-dimensional particles that have the function of changing the electrical properties of an adhesive layer having a vertical alignment force, such as imparting electrical conductivity or a predetermined dielectric constant value to the adhesive layer having a vertical alignment force.
[0137] Ultimately, the effect of reducing the driving voltage of the variable transmittance device varies depending on whether or not the functional nanoparticles are contained and the range of their content.
[0138] In one example, the adhesive layer having vertical alignment power may contain functional nanoparticles at a ratio of 0.005% by weight to 60% by weight. In a specific example, the adhesive layer having vertical alignment power may contain functional nanoparticles at a ratio of 0.05% by weight to 50% by weight or 0.1% by weight to 40% by weight. Within the above range, the desired driving voltage reduction characteristic can be ensured.
[0139] The type of the functional nanoparticles is not particularly limited as long as they satisfy the above-mentioned definition and can provide a display element with a driving voltage reduction characteristic. Examples of the functional nanoparticles include conductive nanoparticles and dielectric nanoparticles.
[0140] In the present application, the term "conductive particles" refers to particles that are electrically conductive and exhibit a certain electrical conductivity. Although the conductive particles are referred to as particles for convenience, the shape and pattern of the conductive particles are not particularly limited.
[0141] The conductive particles are for imparting a predetermined electrical conductivity to the adhesive layer having a vertical alignment force, and are, for example, 1.0×10 1 In another example, the electrical conductivity is 1.0×10 2 S / m or more, 1.0×10 3 S / m or more, 1.0×10 4 S / m or more, or 1.0×10 5 In consideration of the purpose of imparting high electrical conductivity to an adhesive layer having a vertical alignment force, the upper limit of the electrical conductivity of the conductive particles is not particularly limited, but may be, for example, 1.0×10 12 It may be less than S / m.
[0142] In this application, the term "dielectric particles" refers to particles that are a material that has the function of retaining electricity and have a certain dielectric constant. Although the dielectric particles are referred to as particles for convenience, the shape and pattern of the dielectric particles are not particularly limited.
[0143] The shape of the functional nanoparticles may be not only a particle shape, but also a tube, wire, rod, or ring shape.
[0144] In one example, the functional nanoparticles may have a spherical nanoparticle, nanotube, nanowire, nanorod, or nanoring shape, where the term "nanoring" refers to a spherical nanoparticle or a nanostructure that is generally ring-shaped including a hollow portion.
[0145] In one example, the functionalized nanoparticles can be spherical nanoparticles. Specifically, examples of the functional nanoparticles include, but are not limited to, ITO nanoparticles, Ag nanowires, and silica nanoparticles.
[0146] In the present application, among the functional particles described above, those having suitable compatibility with the substances contained in the adhesive layer described above and physical properties that enable them to be uniformly dispersed in the vertically aligned adhesive layer are appropriately adopted and included in the vertically aligned adhesive layer.
[0147] The vertical alignment adhesive layer of the present application contains the above-mentioned functional nanoparticles in a predetermined content range, so that the vertical alignment adhesive layer can be provided with electrical conductivity characteristics or a predetermined dielectric constant value. Specifically, the vertical alignment adhesive layer can exhibit a predetermined difference in electrical conductivity or dielectric constant depending on whether or not the functional nanoparticles are included.
[0148] In one example, the vertical alignment adhesive layer may include functional nanoparticles to satisfy the following formula 1: [Formula 1] G i ×100≦G N ≦1×1010 S / m In the above formula 1, G N indicates the electrical conductivity value (S / m) of the adhesive layer with vertical alignment force containing functional nanoparticles, and G i indicates the electrical conductivity value (S / m) of the adhesive layer having a perpendicular alignment force that does not contain functional nanoparticles.
[0149] When an adhesive layer having a vertical alignment force satisfying the above formula 1 is included in a transmittance variable device, it is possible to effectively induce the application of an electric field to the light modulation layer, thereby achieving the effect of substantially reducing the cell gap difference, and ultimately achieving the effect of reducing the driving voltage of the transmittance variable device.
[0150] Specifically, the electrical conductivity value that can be achieved by including functional particles having a predetermined electrical conductivity in an adhesive layer having a vertical alignment force is 100 times or more, 110 times or more, 120 times or more, 130 times or more, 140 times or more, or 150 times or more than the electrical conductivity value that can be achieved when no functional particles are included in the adhesive layer having a vertical alignment force. Within the above range, an electric field can be applied to the light modulation layer, and the desired effect of reducing the driving voltage can be achieved.
[0151] More specifically, the electrical conductivity value of the adhesive layer having the vertical alignment force is, for example, 1.0×10 -5 In the above-mentioned range of electrical conductivity, the adhesive layer has a relatively low resistance value as compared to the light modulating layer, and an electric field can be applied to the intermediate layer. In another example, the adhesive layer has an electrical conductivity of 2.0×10 -5 S / m or more, or 2.1×10 -5 The upper limit of the electrical conductivity value is not particularly limited, and may be, for example, 1×10 10 It may be less than S / m.
[0152] In another example, the adhesive layer having a vertical alignment force may include functional nanoparticles to satisfy the following Equation 2. [Formula 2] C i×1.5≦C N <= 50 In the above formula 2, C N denotes the dielectric constant value of the adhesive layer with vertical alignment force containing functional nanoparticles, and C i indicates the dielectric constant value of the adhesive layer having a vertical alignment force that does not contain functional nanoparticles.
[0153] That is, the dielectric constant value that can be achieved by including a predetermined content of functional particles in the adhesive layer having vertical alignment power can be 1.5 times or more, 1.6 times or more, 1.7 times or more, 1.8 times or more, 1.9 times or more, or 2 times or more than the dielectric constant value that can be achieved when the adhesive layer having vertical alignment power does not include functional particles. Within the above range, an electric field can be applied to the light modulation layer, and the desired driving voltage effect can be achieved.
[0154] Specifically, the dielectric constant value of the adhesive layer having vertical alignment power may be, for example, 3.00 or more. Within the above-mentioned dielectric constant range, the adhesive layer has a relatively low resistance value compared to the light modulation layer, and an electric field can be applied to the intermediate layer. In another example, the adhesive layer having vertical alignment power may have a dielectric constant of 3.50 or 3.70 or more. The upper limit of the dielectric constant value is not particularly limited, and may be, for example, 50 or less.
[0155] When the adhesive layer having a vertical alignment force contains functional nanoparticles so as to satisfy the above-mentioned formula 1 or formula 2, the desired driving voltage reduction characteristic of the variable transmittance device can be ensured.
[0156] In one embodiment of the present application, the second substrate layer may be the same as the first substrate layer described above.
[0157] In one embodiment of the present application, the alignment film can be used to determine the initial alignment of the liquid crystal in the light modulating layer. The type of the alignment film to be applied is not particularly limited, and may be, for example, a known rubbing alignment film or a photo-alignment film.
[0158] The alignment direction may be the rubbing direction in the case of a rubbed alignment film, or the direction of the irradiated polarized light in the case of a photo-alignment film, and such an alignment direction may be confirmed by a detection method using a linear polarizing layer. For example, when the light modulation layer of the present application is in a twisted alignment mode such as a TN (Twisted Nematic) mode, if a linear polarizing layer is disposed on one surface and the transmittance is measured while changing the absorption axis of the polarizing layer, the transmittance tends to be low when the absorption axis or transmission axis coincides with the alignment direction of the alignment film, and the alignment direction may be confirmed by a simulation that reflects the refractive index anisotropy of the applied liquid crystal compound. A method for confirming the alignment direction according to the mode of the light modulation layer of the present application is well known.
[0159] In one embodiment of the present application, a method for manufacturing a variable transmittance device is provided, comprising the steps of: preparing a pattern film according to the present application; forming an alignment film on the first base layer on which the spacer pattern of the pattern film is formed so as to cover the spacer pattern to form a first laminate; forming an adhesive layer on top of a laminate of a second base layer and a transparent layer to form a second laminate; stacking the first laminate and the second laminate so that the adhesive layer of the second laminate is in contact with the spacer pattern side of the first laminate; and forming a light modulation layer between the first laminate and the second laminate.
[0160] By using the above-mentioned manufacturing method, the transmittance variable film according to the present application can have a specific laminate structure. EXAMPLES
[0161] The present invention will be described in more detail with reference to the following examples. However, the following examples are merely for illustrating the present invention and are not intended to limit the present invention.
[0162] <Production Example> <Example 1> The curable composition used to form the barrier spacers was prepared in the following manner.
[0163] A curable composition was prepared by mixing a black ball spacer and a darkening material with a binder that includes an ultraviolet-curable acrylate compound, a polymerization initiator, and a dispersant and is generally used in the manufacture of partition wall spacers. At this time, as the black ball spacer, a black ball spacer (manufacturer: Sekisui Chemical, product name: KBN508) having an average particle size of about 8 μm, a CV (Coefficient of Variation) of 4, and a standard deviation of the particle size of about 0.32 μm was used. The black ball spacer was mixed at 2.5 parts by weight relative to 100 parts by weight of the binder. In addition, carbon black, as a darkening material, was mixed in a ratio of about 3% by weight in the material. The optical density (OD) of the prepared composition was confirmed to be about 1.36.
[0164] The prepared curable composition was dropped in an amount of 2 mL to 3 mL onto a uniaxially stretched substrate film (PET, Poly(ethylene terephthalate)) on the surface of which an amorphous ITO (Indium Tin Oxide) electrode layer was formed, and the dropped mixture was pressed using a mask to form a laminate including a substrate layer, an electrode layer, a curable composition layer, and a mask. In this state, ultraviolet light was irradiated toward the mask to cure the curable composition layer. (UV irradiation dose: 320 mJ / cm 2 )
[0165] The mask used was a mask in which a patterned light-shielding layer (AgX, X=Cl, F, Br, or I) and a release layer were sequentially formed on a transparent substrate film, a PET film, as shown in FIG. 6. The light-shielding layer pattern had a square arrangement rule. For example, it was assumed that 100 dots were arranged at regular intervals (normal pitch) of 250 μm on a substrate layer having a total area of about 10 mm (normal arrangement state). At this time, the cross-sectional area of the bottom of each dot was adjusted to about 10 μm. Then, the individual dots were connected with lines to form a square-arranged partition spacer pattern (mesh pattern) with a line width of about 10 μm.
[0166] After the UV irradiation, the uncured curable composition was removed (developed) to form a barrier spacer. FIG. 1 is a cross-sectional view of a pattern film having a spacer pattern formed thereon, which was manufactured in the above manner. As shown in FIG. 1, the barrier spacer is embedded with black ball spacers to form a spacer pattern in which the spacer pattern is partially embedded or in contact with the black ball spacers. The height of the manufactured barrier spacer was about 8.2 μm to 8.4 μm, with an average of about 8.3 μm, and the line width was about 15 μm to 21 μm, with an average of about 17.6 μm.
[0167] The ratio of the area where the rectangular partition spacer pattern (Mesh pattern) was present on the surface of the first base layer was about 13.6%. The standard deviation of the height of the spacer pattern was about 0.1 μm, and the standard deviation of the diameter of the ball spacers was about 0.95 μm.
[0168] 7 shows optical microscope images at a magnification of 50 and a magnification of 200, and diffraction evaluation results of the patterned film according to Example 1 of the present application. Specifically, the optical microscope images show that the patterned film includes a regular rectangular spacer pattern including ball spacers and barrier rib spacers, and that the pattern is manufactured without over-curing or breaks in the pattern that may occur around the spacer pattern.
[0169] <Example 2> A pattern film was formed in the same manner as in Example 1, except that the mask design was changed (the pitch of the light-shielding layer pattern was 350 μm).
[0170] The height of the manufactured barrier rib spacer was measured to be about 8.2 μm to 8.4 μm with an average of about 8.3 μm, and the line width was measured to be about 14 μm to 18 μm with an average of about 16.1 μm.
[0171] The ratio of the area where the rectangular partition spacer pattern (Mesh pattern) was present on the surface of the first base layer was about 9%. The standard deviation of the height of the spacer pattern was about 0.1 μm, and the standard deviation of the diameter of the ball spacers was about 0.7 μm.
[0172] 8 shows optical microscope images at a magnification of 50 and a magnification of 200, and diffraction evaluation results of the patterned film according to Example 2 of the present application. Specifically, the optical microscope images show that the patterned film includes a regular rectangular spacer pattern including ball spacers and barrier rib spacers, and that the pattern is manufactured without over-curing or breaks in the pattern that may occur around the spacer pattern.
[0173] <Comparative Example 1> A pattern film was formed in the same manner as in Example 1, except that the mask design was changed (line width of the light-shielding layer pattern was 13 μm).
[0174] The height of the manufactured barrier rib spacer was measured to be about 8.2 μm to 8.4 μm with an average of about 8.3 μm, and the line width was measured to be about 20 μm to 25 μm with an average of about 22.4 μm.
[0175] The ratio of the area where the rectangular partition spacer pattern (Mesh pattern) was present on the surface of the first base layer was about 17.1%. The standard deviation of the height of the spacer pattern was about 0.1 μm, and the standard deviation of the diameter of the ball spacers was about 1.0 μm.
[0176] 9 shows optical microscope images at a magnification of 50 and a magnification of 200, and diffraction evaluation results of the patterned film according to Comparative Example 1 of the present application. Specifically, the optical microscope images show that the patterned film includes a regular rectangular spacer pattern including ball spacers and barrier rib spacers, and that hardened areas due to over-curing that may be formed around the spacer pattern are observed.
[0177] <Comparative Example 2> A pattern film was formed in the same manner as in Example 1, except that the mask design was changed (the pitch of the light-shielding layer pattern was 1100 μm).
[0178] The height of the manufactured barrier rib spacer was measured to be about 8.2 μm to 8.4 μm with an average of about 8.3 μm, and the line width was measured to be about 20 μm to 25 μm with an average of about 22.4 μm.
[0179] The ratio of the area where the rectangular partition spacer pattern (Mesh pattern) was present on the surface of the first base layer was about 4.0%. The standard deviation of the height of the spacer pattern was about 0.1 μm, and the standard deviation of the diameter of the ball spacers was about 0.98 μm.
[0180] 10 shows optical microscope images at a magnification of 50 and a magnification of 200, and diffraction evaluation results of the patterned film according to Comparative Example 2 of the present application. Specifically, the optical microscope images show that the patterned film includes a regular rectangular spacer pattern including ball spacers and barrier rib spacers, and that the pattern is manufactured without over-curing or breaks in the pattern that may occur around the spacer pattern.
[0181] <Device Evaluation of Example 1, Example 2, Comparative Example 1, and Comparative Example 2> A vertical alignment film (Nissan, 5661LB3) was coated on the rectangular arrangement barrier spacer pattern film of Example 1, Example 2, Comparative Example 1 and Comparative Example 2, and dried (100° C.). A vertical alignment film (JSR, R4) was formed on not only the pattern but also the electrode layer of a uniaxially stretched PET (polyethylene terephthalate) base film having an amorphous ITO (indium tin oxide) electrode layer formed on the surface, to form a first laminate.
[0182] Thereafter, an adhesive having a vertical alignment force (Si-OCA: Shin-Etsu Chemical, product name: KR-3700) was applied to the ITO layer on the second substrate layer and dried to prepare a second laminate.
[0183] The first and second laminates thus formed were arranged facing each other while maintaining a gap therebetween using the spacer pattern, and a liquid crystal composition was injected into the gap, after which the edges were sealed to manufacture a variable transmittance device.
[0184] The liquid crystal composition was injected by a lamination method, and a mixed liquid crystal (liquid crystal: JNC, product name: SHN-7002XX T12 / chiral additive: Merck, product name: S811 / dye: BASF, product name: X12) was used as the liquid crystal composition.
[0185] The appearance of the manufactured transmittance variable device was evaluated by applying 40 V using a power supply (Kikusi, PCR500M). Specifically, Fig. 11 is a diagram showing the appearance of the transmittance variable device to which the pattern film of Example 1 is applied when 40 V is applied, Fig. 12 is a diagram showing the appearance of the transmittance variable device to which the pattern film of Example 2 is applied when 40 V is applied, Fig. 13 is a diagram showing the appearance of the transmittance variable device to which the pattern film of Comparative Example 1 is applied when 40 V is applied, and Fig. 14 is a diagram showing the appearance of the transmittance variable device to which the pattern film of Comparative Example 2 is applied when 40 V is applied.
[0186] It was confirmed that the variable transmittance devices using the pattern films of Examples 1 and 2 had a clean appearance without alignment defects, but in the case of Comparative Example 1, it was confirmed that black spots due to alignment defects were observed due to the formation of hardened areas caused by the over-curing phenomenon, and in the case of Comparative Example 2, it was confirmed that the over-curing phenomenon did not occur, but a large number of black spots were generated due to non-uniformity of the alignment film coating due to the low pattern area ratio of the spacer pattern of the pattern film.
[0187] <Example 3> The manufacturing process of the pattern film is the same as that of Example 1, and the differences in the components (light-shielding layer mask design, ball spacer, optical density of the composition, etc.) are as follows:
[0188] A curable composition was prepared by mixing a black ball spacer and a darkening material with a binder that includes an ultraviolet-curable acrylate compound, a polymerization initiator, and a dispersant and is generally used in the manufacture of partition wall spacers. At this time, as the black ball spacer, a black ball spacer (manufacturer: Sekisui Chemical, product name: KBN506) having an average particle size of about 6 μm, a CV (Coefficient of Variation) of 4, and a standard deviation of particle size of about 0.24 μm was used. The black ball spacer was mixed at 2.5 parts by weight relative to 100 parts by weight of the binder. In addition, carbon black, as a darkening material, was mixed in a ratio of about 3% by weight in the material. The optical density (OD) of the prepared composition was confirmed to be about 1.0.
[0189] The mask used was a mask in which a patterned light-shielding layer (AgX, X=Cl, F, Br, or I) and a release layer were sequentially formed on a transparent substrate film, a PET film, as shown in FIG. 6. The light-shielding layer pattern was in a hexagonal arrangement. For example, it was assumed that 100 dots were arranged at regular intervals (normal pitch) of 940 μm on a substrate layer with a total area of about 10 mm (normal arrangement state). At this time, the cross-sectional area of the bottom of each dot was adjusted to about 65 μm. Then, the individual dots were connected with lines to form a rectangular arrangement of partition spacer patterns (mesh patterns) with line widths of about 65 μm.
[0190] The height of the manufactured hexagonal arranged barrier rib spacers was measured to be about 6.1 μm to 6.3 μm with an average of about 6.2 μm, and the line width was measured to be about 70 μm to 76 μm with an average of about 73.7 μm.
[0191] The ratio of the area where the hexagonal spacer pattern (honeycomb pattern) was present on the surface of the first base layer was about 15.1%. The standard deviation of the height of the spacer pattern was about 0.1 μm, and the standard deviation of the diameter of the ball spacers was about 1.0 μm.
[0192] 15 shows optical microscope images at a magnification of 50 and a magnification of 200, and diffraction evaluation results of the patterned film according to Example 3 of the present application. Specifically, the optical microscope images show that the patterned film includes a regular hexagonal spacer pattern including ball spacers and barrier rib spacers, and some hardened areas due to over-curing that may be formed around the spacer pattern were observed, but only at some intersections, and it was confirmed that the patterned film was manufactured without breaks.
[0193] <Example 4> A pattern film was formed in the same manner as in Example 3, except that the mask design (line width of the light-shielding layer pattern: 41 μm) was changed.
[0194] The height of the manufactured barrier rib spacer was measured to be about 6.1 μm to 6.3 μm with an average of about 6.2 μm, and the line width was measured to be about 42 μm to 48 μm with an average of about 45.6 μm.
[0195] The ratio of the area where the hexagonal spacer pattern (honeycomb pattern) was present on the surface of the first base layer was about 9.5%. The standard deviation of the height of the spacer pattern was about 0.1 μm, and the standard deviation of the diameter of the ball spacers was about 0.9 μm.
[0196] 16 shows optical microscope images at a magnification of 50 and a magnification of 200, and a diffraction evaluation result of the patterned film according to Example 4 of the present application. Specifically, the optical microscope images show that the patterned film includes a regular hexagonal spacer pattern including ball spacers and barrier rib spacers, and some hardened areas due to over-curing that may be formed around the spacer pattern are observed, but only at some intersections, and it can be seen that the patterned film is manufactured without breaks.
[0197] <Comparative Example 3> A pattern film was formed in the same manner as in Example 3, except that the mask design was changed (line width of the light-shielding layer pattern was 21 μm, pitch was 280 μm).
[0198] The height of the manufactured barrier rib spacer was measured to be about 6.1 μm to 6.3 μm with an average of about 6.2 μm, and the line width was measured to be about 35 μm to 41 μm with an average of about 38.3 μm.
[0199] The ratio of the area where the hexagonal spacer pattern (honeycomb pattern) was present on the surface of the first base layer was about 25.5%. The standard deviation of the height of the spacer pattern was about 0.1 μm, and the standard deviation of the diameter of the ball spacers was about 0.9 μm.
[0200] 17 shows optical microscope images at 50x and 200x magnifications and diffraction evaluation results of the patterned film according to Comparative Example 3. Specifically, the optical microscope images show that the patterned film includes a regular rectangular spacer pattern including ball spacers and barrier rib spacers, and that hardened areas due to over-curing that may be formed around the spacer patterns are observed.
[0201] <Comparative Example 4> A pattern film was formed in the same manner as in Example 3, except that the mask design was changed (line width of the light-shielding layer pattern was 21 μm, pitch was 1169 μm).
[0202] The height of the manufactured barrier rib spacer was measured to be about 6.1 μm to 6.3 μm with an average of about 6.2 μm, and the line width was measured to be about 25 μm to 35 μm with an average of about 27.7 μm.
[0203] The ratio of the area where the hexagonal spacer pattern (honeycomb pattern) was present on the surface of the first base layer was about 4.7%. The standard deviation of the height of the spacer pattern was about 0.1 μm, and the standard deviation of the diameter of the ball spacers was about 0.9 μm.
[0204] 18 shows optical microscope images at 50x and 200x magnifications and diffraction evaluation results of the patterned film according to Comparative Example 4 of the present application. Specifically, the optical microscope images show that the patterned film includes a regular rectangular spacer pattern including ball spacers and barrier rib spacers, and that the pattern is manufactured without over-curing or breaks in the pattern that may occur around the spacer pattern.
[0205] <Device Evaluation of Example 3, Example 4, Comparative Example 3, and Comparative Example 4> The variable transmittance films were manufactured in the same manner as in Examples 1, 2, Comparative Examples 1 and 2, except that the hexagonally arranged partition wall spacer pattern films of Examples 3, 4, Comparative Examples 3 and 4 were used.
[0206] The appearance of the manufactured variable transmittance device was evaluated in a state before applying 40 V (OV) using a power supply (Kikusi, PCR500M). Specifically, Fig. 19 is a diagram showing the appearance of the variable transmittance device to which the pattern film of Example 3 is applied in a state before applying 40 V (OV), Fig. 20 is a diagram showing the appearance of the variable transmittance device to which the pattern film of Example 4 is applied in a state before applying voltage (OV), Fig. 21 is a diagram showing the appearance of the variable transmittance device to which the pattern film of Comparative Example 3 is applied in a state before applying voltage (OV), and Fig. 22 is a diagram showing the appearance of the variable transmittance device to which the pattern film of Comparative Example 4 is applied in a state before applying voltage (OV).
[0207] It was confirmed that the variable transmittance devices using the pattern films of Examples 3 and 4 had a clean appearance without any alignment defects, but in the case of Comparative Example 3, it was confirmed that black spots due to alignment defects were observed due to the formation of hardened areas caused by the over-curing phenomenon, and in the case of Comparative Example 4, although the over-curing phenomenon did not occur, poor brightness contrast occurred due to uneven liquid crystal height, and it was confirmed that this was due to the difference in liquid crystal height between the pattern part and the center part between the patterns, which was caused by the tilting phenomenon of the pattern film due to the low pattern area ratio. [Explanation of symbols]
[0208] 10: First base layer 20: Partition spacer 30: Ball spacer 40: Alignment film 50: Light modulation layer 60: Adhesive layer 70: Transparent layer 80: Second base layer
Claims
1. A first substrate layer; A plurality of spacer patterns formed on the first base layer; A pattern film comprising: the spacer pattern includes barrier rib spacers and ball spacers; The ball spacer is embedded, partially embedded or in contact with at least one of the partition spacers, a unit area ratio of the spacer pattern to a unit area of the first base layer is 5% or more and 17% or less; the optical density of the spacer pattern is 0.5 or more and 3.5 or less; the plurality of spacer patterns have an irregularity of 50% or more and less than 90%; The line width (T) of the partition spacer and the average particle size (D) of the ball spacers satisfy the following formula 1: [Formula 1] 1.0≦T / D≦20 Pattern film.
2. The patterned film according to claim 1 , wherein the first substrate layer is an inorganic substrate layer or an organic substrate layer.
3. 3. The patterned film according to claim 1, wherein the line width of the spacer pattern is 10 μm or more and 200 μm or less.
4. 4. The pattern film according to claim 1, wherein the average height (H) of the partition spacers is 2 μm or more and 100 μm or less, and the standard deviation of the height of the partition spacers is 0.05 μm or more and 0.5 μm or less.
5. 5. The pattern film according to claim 1, wherein the standard deviation of particle size of the ball spacers is 0.8 μm or less.
6. The pattern film according to any one of claims 1 to 5, a second substrate disposed opposite the pattern film and spaced apart from the pattern film by the spacer pattern of the pattern film; A variable transparency device comprising:
7. The second substrate includes a second base layer and A transparent layer formed on the second base layer; an adhesive layer provided on a surface of the transparent layer opposite to a surface in contact with the second base layer; Including, The variable transmittance device according to claim 6 , wherein the adhesive layer contacts the spacer pattern side.
8. The variable transmittance device according to claim 6 or 7, further comprising an alignment film provided to cover the spacer pattern of the pattern film.
9. The variable transmittance device according to any one of claims 6 to 8, further comprising a light modulating layer provided at a position where a distance from the pattern film is maintained by the spacer pattern.
10. The variable transmittance device of claim 7 , wherein the adhesive layer comprises an adhesive or pressure sensitive adhesive having a vertical orientation force.
11. 10. The variable transmittance device of claim 9, wherein the light modulating layer comprises a liquid crystal compound and a dichroic dye.
12. A step of forming a first laminate by forming an alignment film on the first base layer on which the spacer pattern of the pattern film according to any one of claims 1 to 5 is formed, so as to cover the spacer pattern; forming an adhesive layer on an upper portion of the laminate including the second substrate layer and the transparent layer to form a second laminate; laminating the first laminate and the second laminate such that the adhesive layer of the second laminate contacts the spacer pattern side of the first laminate; forming a light modulating layer between the first stack and the second stack; A method for manufacturing a variable transmittance device comprising:
Citation Information
Patent Citations
Multilayer liquid crystal device
EP0022311A1
A chiral nematic liquid crystal light shutter
EP2998786A1
Liquid crystal display element
JP1998253966A
Liquid crystal display element and its manufacture
JP2000155321A
Liquid crystal display device and method for manufacturing the same
JP2002148636A